BRCA-associated hereditary male cancers: can gender affect the prevalence and spectrum of germline pathogenic variants? - Fanale, Daniele; Corsini, Lidia Rita; Brando, Chiara; Randazzo, Ugo; Bono, Marco; Pedone, Erika; Perez, Alessandro; Sciacchitano, Roberta; Cancelliere, Daniela; Piraino, Paola; Giurintano, Ambra; Bazan Russo, Tancredi Didier; et al. (Frontiers in Oncology, 2024)
Introduction Although hereditary male neoplasms are quite rare, individuals harbouring germline BRCA1/2 pathogenic variants (PVs) may have a risk of developing tumours associated with Hereditary Breast and Ovarian Cancer (HBOC) syndrome, including male breast (MBC), prostate (PCa) and pancreatic (PC) cancers, and melanoma. Women and men showed a comparable genetic architecture of cancer susceptibility, but there are some gender-specific features. Since little is known about cancer genetic susceptibility in male population, our study was aimed at investigating the frequency of BRCA1/2 PVs in men with HBOC syndrome-associated tumors, in order to understand whether differences in gender may reflect in the prevalence and spectrum of germline alterations. Patients and methods We retrospectively collected and analysed clinical information of 352 HBOC-associated male cancer patients genetically tested for germline BRCA1/2 PVs by Next-Generation Sequencing analysis, enrolled, from February 2018 to January 2024, at the “Regional Center for the prevention, diagnosis and treatment of rare and heredo-familial tumors of adults” of the University-Hospital Policlinico “P. Giaccone” of Palermo (Italy). Results Our investigation revealed that 7.4% of patients was carrier of a germline BRCA PV, with an almost total prevalence of BRCA2 alterations. In particular, 65.4% of BRCA-positive patients developed MBC, 19.2% had PC, 11.6% developed PCa, and only 3.8% had melanoma. Specifically, MBC individuals showed a BRCA-associated genetic predisposition in 17% of cases, whereas patients with PCa or PC exhibited a lower frequency of BRCA2 PVs, taking into account the current national criteria for access to germline genetic testing. Discussion Our study showed a high heterogeneity in prevalence of germline BRCA2 PVs among men which could reflect a potential gender-specific genetic heterogeneity. Therefore, BRCA-associated male tumours could be due to BRCA2 PVs different from those usually detected in women. In the event that it is demonstrated, in future, that male cancers are genetically distinct entities from those female this could improve personalized risk evaluation and guide therapeutic choices for patients of both sexes, in order to obtain a gender equality in cancer care.